Jerusalem and the question of bargaining in the Ayyubid Crusader negotiations during the Fifth, Sixth and Seventh Crusades - Alastal, Mohammed Hidar (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify Jerusalem and the issue of bargaining in the Ayyubid Crusader negotiations during the Fifth, Sixth and Seventh Crusades, where Jerusalem played a pivotal and central role in the Islamic Crusader conflict during the Crusades, especially during the Ayyubid era due to its religious importance to Muslims, not only to kings and princes, but Also to the general public for what it represented from a religious ideological aspect, as Jerusalem was the focus of the conflict during the Crusades during the era of Salah al-Din al-Ayyubi and after Salah al-Din al-Ayyubi. Saladin fought the Crusaders and liberated Jerusalem and achieved many victories, but after The death of Salah al-Din al-Ayyubi, his legacy was divided among his sons and brothers, this led to a weaker situation than it was during his rule, especially related to the city of Jerusalem, and this had an impact on the course of events later, where the researcher reached the following results: 1.Jerusalem was the focus of the conflict during the Crusades against the Islamic East during the era of Salah al-Din al-Ayyubi. He fought the Crusaders, liberated Jerusalem, achieved many victories, and refused to abandon Jerusalem. 2. Despite the Muslims’ adherence to Jerusalem, and the Muslims’ rejection of the Crusader occupation; Because Jerusalem holds great importance to the Islamic faith, but personal interest and fear for the seat of power were the reason for bargaining over Jerusalem in the Fifth, Sixth and Seventh Crusades. 3. Some of the Ayyubid rulers bargained to compromise over Jerusalem in their negotiations with the Crusader side, and this appeared in the complete surrender of Jerusalem to the Crusaders, through the Jaffa Agreement, and this is a clear evidence of not adhering to Jerusalem; To maintain the seat of power in Egypt at the time.